Ensino fundamental de nove anos: a docência em escolas da rede municipal de São Carlos - Moraes, Alessandra Cardoso de (Universidade Federal de São Carlos, 2012)
The research deals with the learning processes and the professional development of coordinators and teachers who work in the first year of elementary school considering the expansion of basic education to nine years. The admission of six year old children in compulsory education possibly involves changes in the organization of the pedagogical work developed in the classroom by teachers, as well as some adjustment in the curriculum to meet the specific needs of the newly arriving six year olds. It also requires continued learning programs for teachers, administrators and all other education professionals, which should be guaranteed by the school system. The changes required for the expansion of basic education to nine years as well as for the admission of six year olds at this stage can lead to destabilization, uncertainty and the search for new knowledge about the specific nature, characteristics and needs of six year olds. Thus, this research seeks to understand the ways in which teachers of the first year of elementary school in the Municipality of São Carlos design, develop and implement the policy of extending compulsory education, considering its demands and direct influence on the school and its students. It is important to point out that some aspects of the study are related to what the educational literature says about the learning processes and the professional development of teachers, as well as to what it refers to the expansion of basic education to nine years and the curricular reforms proposed for the first year of basic education. Document analysis, questionnaires and interviews were used for data collection, aiming to understand the conception of the teachers participating in the study about their experiences: the policy in place, participation in continued education programs, the contents to be taught, the encountered difficulties and other aspects that directly influence their perspective on teaching in the first year of basic education. From the analyzed data it is possible to note that this reform involves aspects beyond the implementation of the last policy or guideline adopted by MEC (Ministry of Education), considering a necessary change in both classroom and school cultures. Fear, insecurity and apprehension stemming from the initial expectations of working with six year old children may be justified by the fact that the concept of change is directly associated with rethinking, (re) configuring, (re) organizing the teacher know-how. In this perspective, collective actions aiming to overcome the practical problems encountered in teacher know-how are noteworthy, given that the meaning of change is tied to what those involved can come to understand about what must change and how to do it.
Keywords: Professores - formação; Aprendizagem profissional da docência; Políticas públicas; Ensino fundamental; Ensino fundamental de nove anos; Teacher education; Teachers learning processes; Public policies; Nine year basic education; CIENCIAS HUMANAS::EDUCACAO